Programma: 8 februari Rare Earth; 11 februari Yellowman; 13 februari Ian Hunter & Mick Ronson; 14 februari 999
Programma: 8 februari Rare Earth; 11 februari Yellowman; 13 februari Ian Hunter & Mick Ronson; 14 februari 999.